Internal policy measures to facilitate the integration of smaller economies into the Free Trade Area of the Americas (ECLAC Port-of-SpainTT, 1996)
Looks at monetary , fiscal and trade policies. Focuses on the investment climate and institutional development.
Bibliography: p.20. Additional copy located in the Office of the Secretary General